The last brother - Appanah, Nathacha 1973-; Strachan, Geoffrey (Minneapolis, Minnesota Graywolf Press, 2011)
"As 1944 comes to a close, nine-year-old Raj is unaware of the war devastating the rest of the world. He lives in Mauritius, a remote island in the Indian Ocean, where survival is a daily struggle for his family. After a brutal beating lands Raj in the hospital of a prison camp, he meets David, a boy his own age. David is a refugee, one of a groups of Jewish exiles now indefinitely detained in Mauritius. When a massive storm on the island brings chaos and confusion to the camp, Raj is determined to help David escape."--Page [4] of cover.
Translation of: Le dernier frère.